The Transformation of Private Law Through Competition. Issue 5 (September 2016) - Micklitz, Hans‐W.
Abstract: This paper traces the changing role of competition and its effects on private law in three different stages of the Internal Market project: (1) the promotion of competition in the original Internal Market both via contracts (competitive contract law) and through competition among legal orders (Common European Sales Law); (2) the suspension of competition in the face of financial crisis; and (3) the revitalisation of competition in the Digital Single Market. Private law—broadly understood as regulatory private law—is being deployed to achieve competing, if not conflicting, policy goals. At this stage, it is not possible, nor would it be desirable, to provide a coherent account of these phenomena. Clear‐cut overarching values cannot be identified either. Transformation through competition is just another take on European experimentalism.